Relationship between hippocampal subfield volumes and cognitive decline in healthy subjects - Doran, Simon; Carey, Daniel; Knight, Silvin; Meaney, James F.; Kenny, Rose Anne; De Looze, Céline (Frontiers in Aging Neuroscience, 2023)
We examined the relationship between hippocampal subfield volumes and cognitive decline over a 4-year period in a healthy older adult population with the goal of identifying subjects at risk of progressive cognitive impairment which could potentially guide therapeutic interventions and monitoring. 482 subjects (68.1 years +/− 7.4; 52.9% female) from the Irish Longitudinal Study on Ageing underwent magnetic resonance brain imaging and a series of cognitive tests. Using K-means longitudinal clustering, subjects were first grouped into three separate global and domain-specific cognitive function trajectories; High-Stable, Mid-Stable and Low-Declining. Linear mixed effects models were then used to establish associations between hippocampal subfield volumes and cognitive groups. Decline in multiple hippocampal subfields was associated with global cognitive decline, specifically the presubiculum (estimate −0.20; 95% confidence interval (CI) -0.78 – −0.02; p = 0.03), subiculum (−0.44; −0.82 – −0.06; p = 0.02), CA1 (−0.34; −0.78 – −0.02; p = 0.04), CA4 (−0.55; −0.93 – −0.17; p = 0.005), molecular layer (−0.49; −0.87 – −0.11; p = 0.01), dentate gyrus (−0.57; −0.94 – −0.19; p = 0.003), hippocampal tail (−0.53; −0.91 – −0.15; p = 0.006) and HATA (−0.41; −0.79 – −0.03; p = 0.04), with smaller volumes for the Low-Declining cognition group compared to the High-Stable cognition group. In contrast to global cognitive decline, when specifically assessing the memory domain, cornu ammonis 1 subfield was not found to be associated with low declining cognition (−0.14; −0.37 – 0.10; p = 0.26). Previously published data shows that atrophy of specific hippocampal subfields is associated with cognitive decline but our study confirms the same effect in subjects asymptomatic at time of enrolment. This strengthens the predictive value of hippocampal subfield atrophy in risk of cognitive decline and may provide a biomarker for monitoring treatment efficacy.